PENGAJARAN DOKKAI MENGGUNAKAN APLIKASI MIGII - Miranti Artarina (Jurnal Sastra - Studi Ilmiah Sastra, 2023)
This study aims to evaluate the effectiveness of teaching dokkai or reading in Japanese using the MIGII technology-based learning application. As technology continues to develop, Japanese language learning apps offer innovative solutions to improve students' reading skills. This study was conducted to assess the impact of using these learning applications in the context of teaching dokkai to beginners.The research methodology involved selecting participants consisting of novice students learning Japanese. Participants were divided into two groups, one group used the MIGII Japanese language learning application, while the control group used conventional teaching methods. Each group was given a pre-test to measure reading ability before intervention.The results showed that the group that used the MIGII Japanese language learning application experienced significant improvements in reading skills compared to the control group. This application provides a learning environment that is interactive, motivating, and supports the development of students' reading skills.These findings contribute to our understanding of the effectiveness of technology-based Japanese language learning methods, particularly in the context of teaching dokkai. The implications of this research can be used to improve curriculum design and Japanese language teaching, by exploiting the potential of learning applications to provide more effective and engaging learning experiences for beginners.Keywords: application, dokkai, migii, reading, Japanese